Role of Histone Post-Translational Modifications in Inflammatory Diseases - Lin, Yingying; Qiu, Ting; Wei, Guifeng; Que, Yueyue; Wang, Wenxin; Kong, Yichao; Xie, Tian; Chen, Xiabin (Frontiers in Immunology, 2022)
Inflammation is a defensive reaction for external stimuli to human body and generally accompanied by immune responses, which is associated with multiple diseases such as atherosclerosis, type 2 diabetes, Alzheimer’s disease, psoriasis, asthma, chronic lung diseases, inflammatory bowel disease, and multiple virus-associated diseases. Epigenetic mechanisms have been demonstrated to play key role in the regulation of inflammation. Common epigenetic regulations are DNA methylation, histone modifications and non-coding RNA expression, among these, histone modifications embrace various post-modifications including acetylation, methylation, phosphorylation, ubiquitination, ADP ribosylation, etc. This review focus on the significant role of histone modifications in the progression of inflammatory diseases, providing the potential target for clinical therapy of inflammation-associate diseases.